Can intraoperative suturing reduce the incidence of posttonsillectomy hemorrhage? A systematic review and meta‐analysis. Issue 4 (23rd June 2022) - Li, Bo; Wang, Miaowei; Wang, Yanwen; Zhou, Lingyun
Abstract: Objective: This study was to compare tonsillectomy with intraoperative suturing (TIS) and tonsillectomy without intraoperative suturing (TsIS) in preventing postoperative tonsillectomy hemorrhage (PTH). Methods: The Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines was followed. Articles compare TIS and TsIS in preventing PTH were included. The quality of eligible studies was assessed with the Newcastle‐Ottawa Scale (NOS) by two independent investigators. Random effect models were used to determine odds ratio (OR) with 95% CIs. Results: A total of 15 studies were analyzed. The pooled results showed the PTH rate was lower in the TIS group (OR = 0.64; 95% CI, 0.47–0.88). The TIS group had a lower primary and secondary PTH rate than the TsIS group with OR values of 0.44 (95% CI, 0.30–0.64) and 0.70 (95% CI, 0.54–0.90), respectively. However, suturing did not show an advantage in reducing the risk of returning to the operation room for hemostasis (OR = 0.57; 95% CI, 0.13–2.47). Adults might benefit from the intraoperative suturing procedure (OR = 0.31; 95% CI, 0.16–0.60). Patients with more than three stitches on each side had a lower PTH rate (OR: 0.44; 95% CI, 0.32–0.60). Suturing the tonsillar fossa and pillars simultaneously could reduce the PTH rate (OR = 0.47; 95% CI, 0.34–0.64). Conclusions: Intraoperative suturing is a good strategy for preventing PTH. More multicenter randomized controlled studies should be conducted to demonstrate the efficacy of this procedure. Level of Evidence: 5. Abstract : Postoperative tonsillectomy hemorrhage (PTH) is a rare but crucial complication, which can be life‐threatening, and might necessitate an emergency operation. Surgical details such as suturing methods might influence PTH risk. Intraoperative suturing is a good strategy for preventing PTH.